2022
DOI: 10.1289/ehp9833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Biomarkers of Atherosclerosis Associated with Polychlorinated Biphenyl Exposure: An in Vitro and in Vivo Study

Abstract: Background: Miscellaneous cardiovascular risk factors have been defined, but the contribution of environmental pollutants exposure on cardiovascular disease (CVD) remains underappreciated. Objective: We investigated the potential impact of typical environmental pollutant exposure on atherogenesis and its underlying mechanisms. Methods: We used human umbilical vein endothelial cells (HUVECs) and apolipoprotein E knockout ( ) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 102 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…CVDs remain the leading cause of death and disability globally, and the risk factor characterization including environmental pollution deserved an urgent investigation . As one of the most widely used chemical compounds in daily consumer products, synthetic bisphenols have traditionally been recognized as an environmental health risk factor mainly as typical EDCs with steroid hormonal effects. Epidemiological and animal data support the potential involvement of bisphenol exposure as for disrupting arterial health and developing CVD risk in humans. , Recent research suggested that the maternal bisphenol exposure level might influence fetal vascular development .…”
Section: Discussionmentioning
confidence: 99%
“…CVDs remain the leading cause of death and disability globally, and the risk factor characterization including environmental pollution deserved an urgent investigation . As one of the most widely used chemical compounds in daily consumer products, synthetic bisphenols have traditionally been recognized as an environmental health risk factor mainly as typical EDCs with steroid hormonal effects. Epidemiological and animal data support the potential involvement of bisphenol exposure as for disrupting arterial health and developing CVD risk in humans. , Recent research suggested that the maternal bisphenol exposure level might influence fetal vascular development .…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, Cav1 deficiency has been shown to reduce AS and plaque inflammation by reducing leukocyte influx and systemic anti-inflammatory T lymphocytes [ 125 ]. In AS induced by PCB29-PQ (a metabolite of the typical environmental pollutant PCB), Cav1 can act as a scaffold for inflammatory signaling by negatively regulating TGF-β and Cav1 phosphorylation to activate pro-inflammatory ROS [ 127 ]. Cav1 activates cellular inflammatory states through various signaling pathways.…”
Section: Effect Of Cav1 On Endothelial Cells In Asmentioning
confidence: 99%